PENGEMBANGAN KOMIK DIGITAL SEX EDUCATION UNTUK SISWA SD DI SD INPRES MANGGA TIGA MAKASSAR - Amelia Dwiputri; Citra Rosalyn Anwar; Farida Febriati (STKIP Subang, 2023)
The problem in this study is that students' understanding of sex education and protecting themselves is still very lacking due to teachers who only teach parts of the body without linking to self-protection, this will have an impact if students know this by themselves or self-taught without direction and without being accompanied by teachers or parents through their smartphones. The objectives in this study are 1) Analyse the needs of Digital Comic products for elementary school students; 2) Knowing the level of validation of Digital Comic products; 3) Knowing the practicality of Digital Comic products. This research was conducted using the approach and type of Research and Development (R&D) research using the ADDIE development model. The subjects of this study were 30 students and one homeroom teacher. The results of this study indicate that 1) Identification of the level of need for the development of Digital Comics is in the qualification needed; 2) The results of testing the validity of digital comics by content/material experts are in very valid qualifications and the results of validation by design/media experts are in very valid qualifications; 3) The results of practicality testing conducted by one homeroom teacher IV-A are in very practical qualifications and trials on elementary school students in class IV-A consisting of 30 students obtained results that were in very practical qualifications. Based on the results of the analysis, it can be concluded that the Digital Sex Education Comic is very valid and practical to use in the learning process.